The Role of Tax Incentives and Wage Dynamics in Shaping Foreign Direct Investment: A Cambodian Perspective (2009-2023) - Piseth Holl; Chumneanh Lork (MASI Mandiri Edukasi, 2025)
This study examines the impact of tax incentives—specifically those related to Tax on Income (ToI) exemptions—and minimum wage dynamics on foreign direct investment (FDI) inflows in Cambodia, with a focus on the role of Qualified Investment Projects (QIPs). Using descriptive statistics, one-way ANOVA, Tukey’s post hoc test, and multiple regression analysis, the research reveals significant variability in FDI inflows. The results strongly support Hypothesis 1, confirming that tax exemptions (5%, 10%, or 15%) are positively associated with higher FDI, although benefits diminish beyond a 5% exemption. Contrary to Hypothesis 2, a strong positive correlation (r = 0.950, p < 0.001) was found between the minimum wage and FDI, suggesting that rising wages may reflect economic stability and labor quality, thereby encouraging investment. Regression analysis (R² = 0.931, p < 0.001) reveals that both tax exemptions and minimum wage are positively related to FDI; however, only minimum wage demonstrates individual statistical significance (B = 11.586, p = 0.002). These findings offer partial support for Hypothesis 3, indicating that while tax incentives are relevant, wage levels play a more influential role in attracting FDI. The study concludes that a combination of higher minimum wages and generous tax exemptions yields the highest predicted FDI inflows, emphasizing the need for balanced economic policy.